Evaluation of Sanitizing Methods for Reducing Microbial Contamination on Fresh Strawberry, Cherry Tomato, and Red Bayberry - Wei, Wei; Wang, Xu; Xie, Zhongwen; Wang, Wen; Xu, Junfeng; Liu, Yuanjing; Gao, Haiyan; Zhou, Yu (Frontiers in Microbiology, 2017)
Strawberries, cherry tomatoes and red bayberries, which are the most popular types of fresh produce in China, are vulnerable to microbial contamination. In this study, different sanitizing methods [treatment with 2% organic acids, 0.02% sodium hypochlorite (SH), 0.1% sodium chlorite (SC) and 0.1% acidified sodium chlorite (ASC)] were applied to fresh strawberry, cherry tomato and red bayberry, and their abilities to reduce aerobic bacteria, Escherichia coli O157:H7, mold, yeast and Salmonella Typhimurium were evaluated. The commercially used SH method reduced the background microbiota on strawberry, cherry tomato and red bayberry by 0.20–2.07 log cfu/g. The ASC method reduced background microbiota (except for mold) on strawberry and cherry tomato by more than 3.0 log cfu/g. ASC was the only sanitizer that significantly reduced mold on red bayberry, and lactic acid was the only organic acid sanitizer that effectively reduced yeast on red bayberry. The ASC method had the best sterilizing effect on the three fresh fruits and also required the shortest sanitizing time and low chlorite content. The application of ASC method significantly reduced the microbiota on retail grocery samples, and the effect was similar to that achieved by sanitizing methods comparison.